2006
DOI: 10.1038/nature04438
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of extended defects in solid oxide fuel cell anodes for methane oxidation

Abstract: Point defects largely govern the electrochemical properties of oxides: at low defect concentrations, conductivity increases with concentration; however, at higher concentrations, defect-defect interactions start to dominate. Thus, in searching for electrochemically active materials for fuel cell anodes, high defect concentration is generally avoided. Here we describe an oxide anode formed from lanthanum-substituted strontium titanate (La-SrTiO3) in which we control the oxygen stoichiometry in order to break do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
223
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 400 publications
(240 citation statements)
references
References 20 publications
7
223
0
1
Order By: Relevance
“…Randomly distributed dark spots are also visible but no local lattice distortion is observed. [19] Excess [55] The arrows indicate some dark spots, which are the locations of excess oxygen anions. The inset shows an enlarged image of a dark spot.…”
Section: Point Defectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Randomly distributed dark spots are also visible but no local lattice distortion is observed. [19] Excess [55] The arrows indicate some dark spots, which are the locations of excess oxygen anions. The inset shows an enlarged image of a dark spot.…”
Section: Point Defectsmentioning
confidence: 99%
“…Figure 6 (a) shows a typical HRTEM image of La 4 Sr 8 Ti 12 O 38 in a perovskite structure with excess oxygen, with which a high anion conductivity was achieved. [55] Since there is not a large enough space for guest atoms in a perfect perovskite crystal with a formula of ABO 3 , the excess oxygen atoms must go to interstitial sites and build up local lattice strain. The resolution of the electron microscope (JEOL JEM-2010) used is not high enough to image randomly located individual oxygen atoms.…”
Section: Point Defectsmentioning
confidence: 99%
“…4 To overcome these issues, nickel-free metal oxide anode materials have been investigated, such as La 0.75 Sr 0.25 Cr 0.5 Mn 0.5 O 3−δ (LSCM), 5 Sr 2 Mg 1−x Mn x MoO 6−δ (x = 0 to 1), 6 and doped (La, Sr)(Ti)O 3 . 7,8 Experimental results have demonstrated that such anode materials are effective in inhibiting carbon deposition or sulfur poisoning. [9][10][11] So far the cell designs are exclusively electrolyte-supported when metal oxide anodes are employed.…”
mentioning
confidence: 99%
“…INTRODUCTION SrTiO 3 (STO) exhibits a host of interesting phenomena ranging from being a quantum paraelectric insulator 1 to a ferroelectric under strain 2 and a metal 3 or superconductor 4 when doped and hence has been one of most extensively studied perovskite oxides. These diverse properties make it an attractive choice for many applications such as oxidebased electronics, 5 photocatalysis, and as electrodes 6 in solid oxide fuel cells. Recently, the presence of a two-dimensional electron gas at the bare surface of STO 7 and at the interface of the polar STO with non-polar LaAlO 3 (LAO) has been demonstrated, 8 triggering intense research from both fundamental and applications points of view.…”
mentioning
confidence: 99%